PENGARUH METODE STORYTELLING TERHADAP KARAKTER KERJASAMA PADA SISWA KELAS III SD PUJOKUSUMAN YOGYAKARTA - Indah Perdana Sari; Intan Kurniasari Suwandi; Susi Setyowati (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2018)
This study aims to understand the influence of the storytelling method towards the third-grade students’ character in doing cooperation in Pujokusuman Yogyakarta Elementary School. The research is research quasi-experiment with a nonequivalent-group pretest-posttest research design. The subject of the study is the students of class III B and III C Pujokusuman Yogyakarta Elementary School consisted of 49 students. Class III B isconsisted of 24 students and it becomes the class control, while class III C is consisted of 25 students and it becomes the class experiment. The researchers utilized observation sheet as the research instrument. The data analyzing technique was conducted through the first independent sample t-test with the significance 5 % (alpha = 0,05). This research result indicates that storytelling method is significant in increasing the third-grade students’ character in doing cooperation in Pujokusuman Yogyakarta Elementary School. This is proven by the t-test resulted 0,00 < 0,05; so H0 is rejected, it means that there is a significant difference between the average observation result of the students’ character in doing cooperation in the two classes: class control and class experiment. From the research result, it can be concluded that storytelling method enhances the third-grade students’ character value in doing cooperation in Pujokusuman Yogyakarta Elementary School.